Optimizing Field Taxonomy: Development of a Field-Adapted Identification Key to the Rodents of an Afromontane Tropical Rainforest - Majyambere, Methode; Niyodushima, Pacifique; Nsabimana, Antoine (Research in Ecology, 2025)
Identification keys for terrestrial small mammals are often based on scientific details that require close examination of museum specimens. This paper builds on external morphological characteristics of the rodents recorded through live trapping from 2011 to 2023 in Nyungwe National Park, a tropical rainforest in Rwanda, to formulate a taxonomic key suitable for both expert and non-expert researchers working in similar ecosystems across Africa. We reviewed the literature on taxonomic keys and field guide documents for small mammals to assess their practicality and identify gaps, with a special focus on their relevance to tropical regions and our study area. We then integrated our field records to harmonize this new development. We describe 23 rodent species, identified and confirmed using advanced taxonomic techniques, including DNA barcoding and voucher specimens. The study emphasizes that external features—particularly field photographs, body coloration (dorsal, ventral, and lateral views), and other distinctive anatomical traits—can serve as an effective field taxonomic key for rodents and other terrestrial small mammals, accessible to a broad scientific community. The paper also discusses the limitations of traditional dichotomous keys compared to short descriptions paired with photographic illustrations. The resulting key can be used as a template and is open to refinement as additional species are confirmed, re-assessed, or validated through advanced tools. Future studies may adapt this approach for other terrestrial small mammals and different locations across African tropical rainforests.